Managing a Sport Organization: The Impact of Recruiting, Selecting, and Retaining Elite Level Coaches in Sport - Jonathon Edwards; Marvin Washington (Journal of Applied Sports Management, 2013)
Hockey clubs in Edmonton, Alberta, Canada are a fascinating setting to study as they merge issues related to youth sport participation and volunteerism with elite level sport development. We examine the management of elite level hockey clubs, through interviews, to understand how the organizations develop and implement processes that enable them to obtain and maintain a positive reputation through the development of elite level hockey players. The results of our analyses show that hockey clubs view the coach as a vital part of creating and maintaining a successful organizational reputation. This study makes two contributions to the sport management literature; first we extend the literature on recruitment, selecting, and retention to the sport setting by understanding how hockey clubs acquire and retain the services of the most successful and qualified volunteer hockey coaches. Second, we provide a foundation for sport managers, working in a volunteer sport participation environment, to understand how they can compete for a limited pool of successful and qualified coaches.
Keywords: Sport volunteerism; coaching; recruitment processes; selection process; retention process; sport management; elite level sport